Optimizing Hemoglobin Levels in Adolescent Girls Using Iron Tablets and Mung Bean Juice - Lidia Lushinta; Ratanto Ratanto; Jasmawati Jasmawati; Elisa Goretti Sinaga; Cristinawati B/R Haloho; Fara Imelda Theresia Patty; Evy Nurachma (Poltekkes Kemenkes Surakarta, 2026)
Background: Anemia is predominantly attributed to blood loss, particularly in adolescent girls during menstruation, and insufficient consumption of iron-rich foods. Iron-rich food sources include almonds, leafy greens, and red meat. Pharmacological interventions to address low hemoglobin levels in teenagers included the weekly intake of iron tablets, whilst non-pharmacological strategies involved the daily ingestion of mung bean juice. This study sought to assess the impact of iron tablet and mung bean juice administration on hemoglobin level enhancement in adolescent girls at a Junior High School in Samarinda. Methods: The research employed a quasi-experimental approach featuring a nonequivalent control group. The sampling strategy employed a non-probability method via purposive sampling. The researcher established the sampling according to the inclusion and exclusion criteria utilizing the Federer formula, resulting in 18 individuals in both the control and intervention groups. The treatment group received mung bean juice for a duration of 14 days. A paired T-test was used to analyze the difference in hemoglobin levels before and after therapy. Results: The analysis produced a p-value < 0.001, which is less than 0.05, leading to the conclusion that the intervention group exhibited a greater increase in hemoglobin levels compared to the control group. Conclusion: The administration of Fe tablets and mung bean juice effectively increased hemoglobin levels in teenage girls at the Junior High School in Samarinda. Regular administration of iron tablets and mung bean juice is recommended as a measure to increase hemoglobin levels in adolescent girls.